A Clinical, Neuropathological and Genetic Study of Homozygous A467T POLG-Related Mitochondrial Disease. - Sanjeev Rajakulendran; Robert D S Pitceathly; Jan-Willem Taanman; Harry Costello; Mary G Sweeney; Cathy E Woodward; Zane Jaunmuktane; Janice L Holton; Thomas S Jacques; Brian N Harding; Carl Fratter; Michael G Hanna; et al. (PLoS ONE)
Mutations in the nuclear gene POLG (encoding the catalytic subunit of DNA polymerase gamma) are an important cause of mitochondrial disease. The most common POLG mutation, A467T, appears to exhibit considerable phenotypic heterogeneity. The mechanism by which this single genetic defect results in such clinical diversity remains unclear. In this study we evaluate the clinical, neuropathological and mitochondrial genetic features of four unrelated patients with homozygous A467T mutations. One patient presented with the severe and lethal Alpers-Huttenlocher syndrome, which was confirmed on neuropathology, and was found to have a depletion of mitochondrial DNA (mtDNA). Of the remaining three patients, one presented with mitochondrial encephalomyopathy, lactic acidosis and stroke-like episodes (MELAS), one with a phenotype in the Myoclonic Epilepsy, Myopathy and Sensory Ataxia (MEMSA) spectrum and one with Sensory Ataxic Neuropathy, Dysarthria and Ophthalmoplegia (SANDO). All three had secondary accumulation of multiple mtDNA deletions. Complete sequence analysis of muscle mtDNA using the MitoChip resequencing chip in all four cases demonstrated significant variation in mtDNA, including a pathogenic MT-ND5 mutation in one patient. These data highlight the variable and overlapping clinical and neuropathological phenotypes and downstream molecular defects caused by the A467T mutation, which may result from factors such as the mtDNA genetic background, nuclear genetic modifiers and environmental stressors.